Sarcopenic Obesity in Individuals With Neurodisabilities: The SarcObeNDS Study - Dionyssiotis, Yannis; Prokopidis, Konstantinos; Trovas, George; Papadatou, Maria-Christina; Ananidis, Nikolaos; Tragoulias, Vasileios; Lazarou, Eleni; Christaki, Evangelia; Domazou, Marilena; Galanos, Antonios; Tyllianakis, Minos (Frontiers in Endocrinology, 2022)
Introduction Patients with neurodisabilities (NDS) are prone to alterations in body composition. Sarcopenic obesity (SO) is a condition characterised by increased adipose tissue accompanied by sarcopenia. Τhe aim of this study was to investigate the prevalence of SO in patients with NDS, including stroke, spinal cord, and traumatic brain injuries. Methods The study Sarcopenic Obesity in NeuroDisabled Subjects (Acronym: SarcObeNDS) was a cross-sectional study of hospitalized patients (n=82) and healthy controls (n=32) with a mean age 60.00 ± 14.22 years old. SO and sarcopenia were assessed through total body fat % (TBF %), fat mass index (fat mass to height2; FMI=FM/h2; kg/m2) and skeletal muscle index (appendicular skeletal muscle to height2; SMI=ASM/h2; kg/m2) via full body dual-energy x-ray absorptiometry (DXA). This study was registered in the international database ClinicalTrials.gov with unique number: NCT03863379. Results A statistically significant difference was found in SMI (7.18 ± 0.95 kg/m2 vs. 6.00 ± 1.13 kg/m2, p<0.001) between controls and patients with NDS. No statistical significance was found for TBF (p=0.783) and FMI (p=0.143) between groups. The results remained the same after controlling the results for gender and BMI. A strong positive correlation was demonstrated between BMI and TBF for the total population (r=0.616, p<0.001), the control group (r=0.616, p<0.001) and patients with NDS (r=0.728, p<0.001 ) . Conclusion In summary, we observed significantly lower BMI and SMI scores in both genders compared to healthy controls. At the clinical level, a timely diagnosis and rapid treatment of sarcopenia and/or obesity in this population may prevent further metabolic repercussions accompanied by higher functional decline and lower quality of life.